Correlation Of CRP And Blood Culture In Neonatal Sepsis - LANGADE, RAJKUNVAR; PRADHAN, AIESHWARYA (International Journal of Psychosocial Rehabilitation, 2020)
Sepsis in neonates might be hard to separate from different conditions, in light of the fact that the clinical signs are vague. It is a typical reason for bleakness and mortality among neonates in NICU. Delay of even few hours in initiating treatment can increase morbidity and mortality considerably. To determine the level of CRP and blood culture in neonatal septicemia 40 clinically suspected cases of neonatal sepsis admitted to Krishna Institute of Medical Sciences, Karad All neonates who were clinically suspected sepsis, categorized into 0-72 hours (early onset) or late onset (>3 days) sepsis based on day of presentation. Detailed history and clinical findings were recorded in the Performa and screened with CRP and at the same time blood culture was sent. Intrapartum risk factors like prolonged rupture of membrane >24 hrs.Prolonged duration of labour, unclean multiple (>3) per vaginal examination before delivery, foul smelling liquor were significantly associated with culture proven neonatal sepsis. Any of the above two risk factors were good predictors of culture positive sepsis. Higher proportion of low birth weight and prematures were affected by neonatal sepsis. CRP had high sensitivity and good negative predictive value. Klebsiella fallowed by Staphylococcus aureus and E.coli were the commonest isolate. Case fatality was high culture proven (43.9%), low birth weight (41.37%) and preterm babies (44.68%). Intrapartumrisk factors are significantly with culture proven sepsis.Low birth weights are significant risk factors for both early onset and late onsetsepsis. Early onset sepsis is significantly associated with intrapartum risk factors like PROM>24hrs, prolonged duration labour, unclean per vaginal examination and foul smelling liquor Late onset sepsis is more often due to faulty feeding practices & these neonates have some focus of infection like gastroenteritis etc., as risk factor forsepsis. CRP is a good diagnostic and therapeutic tool. This helps to reduce the delay in instituting antibiotictherapy. CRP can be used as an early and predictable screening test for diagnosing Neonatal sepsis.